2009
DOI: 10.1534/genetics.109.109579
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for an Essential Oscillation of Transmembrane-Spanning Segment 5 in the Escherichia coli Ammonium Channel AmtB

Abstract: Ammonium channels, called Amt or Mep, concentrate NH 1 4 against a gradient. Each monomer of the trimer has a pore through which substrate passes and a C-terminal cytoplasmic extension. The importance of the C-terminal extension to AmtB activity remains unclear. We have described lesions in conserved C-terminal residues that inactivate AmtB and here characterize 38 intragenic suppressors upstream of the C terminus ($1/3 of total suppressors). Three that occurred repeatedly, including the previously characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…The W148 variants were exceptions. Previous work indicated that W148 restricts substrate flux, and as is shown here, replacing this residue with L increases CH 3 NH 3 + conductance (2,20). These studies also provided evidence that the W148L substitution improves the rate of NH 4 + transport.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The W148 variants were exceptions. Previous work indicated that W148 restricts substrate flux, and as is shown here, replacing this residue with L increases CH 3 NH 3 + conductance (2,20). These studies also provided evidence that the W148L substitution improves the rate of NH 4 + transport.…”
Section: Resultssupporting
confidence: 84%
“…As has been observed previously (19,20), and for reasons yet to be explored, most active AmtB variants reached a slightly higher final OD 420 than the wild-type strain when grown on low-NH 3 medium.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Based on genetic evidence, an interesting idea was put forward that the C-terminal tail of AmtB facilitates an oscillation of transmembrane segment 5 (TM5) that controls the opening of both the periplasmic gate and the cytoplasmic exit (302). It is tempting to speculate that the synchronized flipping of the Phe gate (285) is related to TM5 oscillation.…”
Section: Ammonium Transportermentioning
confidence: 99%
“…The structure of the CTR was not resolved in the X-ray structures of E. coli AmtB (271,275). Deletion of the entire region substantially reduces AmtB activity to an intermediate (25 to 30%) level (269,302,303) and prevents association with GlnK (303). The addition of PhoA or LacZ peptides to the C terminus completely abolishes methylamine (MA) transport activity (270).…”
Section: Ammonium Transportermentioning
confidence: 99%